Cylindrocladium scoparium Morgan - A New Pathogen of some Forest Tree Species in Peninsular Malaysia - Su see, Lee; Ahmad, Abdul Manap (1982)
Cylindrocladium scoparium Morgan was isolated from seeds of Shorea talura Roxb., Horsfeldia sp. and Maesopsis eminii Engl. Musizi. This fungus has not been previously recorded in Peninsular Malaysia. Inoculation tests showed that Cylindrocladium scoparium was pathogenic to seedlings of Dipterocarpus grandiflorus Blanco, a spe'cies indigenous to Malaysian forests, and Pinus caribaea Mor., an introduced species of tropical pine planted in this country.